OP103 Understanding social inequalities in child mortality: a population-based study in denmark and wales. (3rd September 2019) - Lai, ETC; Griffiths, R; Akbari, A; Urhoj, SK; Andersen, AMN; Taylor-Robinson, DC
Abstract : Background: Children growing up in disadvantaged socioeconomic circumstances (SECs) have a higher risk of death. In this study, we aimed to examine whether perinatal factors mediate the relationship between SECs and child mortality. Methods: We conducted national registry linkage studies in two countries, using data for 592, 001 births in Denmark (from 2000 to 2014) and 646, 303 births in Wales (from 2000 to 2016). Deaths up to age 15 years in Denmark and up to 16.5 years in Wales were identified using death registry data, whilst birth weight and gestational age were obtained using medical birth register data. SECs at child's birth were measured using maternal education in Denmark, which was identified from the Integrated Database for Labour Market Research; whilst in Wales, SECs were assessed based on quintiles of Welsh Index of Multiple Deprivation (WIMD), which was obtained for the mother's postcode from the Welsh Demographics Service Dataset. We built two Cox proportional hazard survival analysis models to estimate the effect of SECs on children mortality and mediation by the perinatal factors: model 1 is the baseline model adjusted for sex and year of birth, model 2 additionally adjusted for birth weight and gestational age. As a sensitivity analysis, we tested whether the effect of SECs on child mortality changes over time, i.e. we assessed the interaction term between SEC measures and birth year. Results: We identified 2, 664 deaths in Denmark and 2, 987 deaths in Wales. In both countries, lower SECs was associated with a higher risk of child mortality [Denmark: Hazard ratio (HR) 2.78; 95% confidence interval (CI): 1.04 to 7.43 (comparing maternal education with lower secondary or lower and those with university degree); Wales: HR: 1.92; 95%CI: 1.56 to 2.36 (comparing whose mothers from most deprived quintile and those from least deprived quintile)]. After adjustment for perinatal factors, the associations were attenuated (Denmark: HR: 1.65, 95%CI: 0.62 to 4.41; Wales: HR: 1.66, 95%CI: 1.35 to 2.05). Sensitivity analysis did not show the effect of SECs on child mortality changes over time. Discussion: Using data from over 1 million children across two countries, we showed that a substantial proportion of social inequality of child mortality could be explained by perinatal factors. Policies to reduce child mortality in both countries should therefore focus on improving maternal health before and during pregnancy, especially those under socioeconomic disadvantage. A limitation of this study is that SEC measures are not directly comparable across countries.